2014
DOI: 10.1021/la500987c
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Interactions of Fusogenic Coiled-Coil Peptides: Implications for Lipopeptide Mediated Vesicle Fusion

Abstract: Fusion of lipid membranes is an important natural process for the intra- and intercellular exchange of molecules. However, little is known about the actual fusion mechanism at the molecular level. In this study we examine a system that models the key features of this process. For the molecular recognition between opposing membranes two membrane anchored heterodimer coiled-coil forming peptides called 'E' (EIAALEK)3 and 'K' (KIAALKE)3 were used. Lipid monolayers and IR reflection absorption spectroscopy (IRRAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
117
2
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(141 citation statements)
references
References 58 publications
(142 reference statements)
20
117
2
2
Order By: Relevance
“…Apparently, the tethered peptide in LPK* is bound stronger to the vesicle than the untethered K*. Similar effects were also observed earlier in a study of the interactions of K, E, LPK, and LPE with lipid monolayers (19).…”
Section: Membrane Binding Of K Before and After Vesicle Dockingsupporting
confidence: 85%
See 2 more Smart Citations
“…Apparently, the tethered peptide in LPK* is bound stronger to the vesicle than the untethered K*. Similar effects were also observed earlier in a study of the interactions of K, E, LPK, and LPE with lipid monolayers (19).…”
Section: Membrane Binding Of K Before and After Vesicle Dockingsupporting
confidence: 85%
“…Recent infrared spectroscopic studies of LPE and LPK containing lipid mono-or bilayers revealed differing behaviors of the two peptides before the fusion commences (19,20). The negatively charged E shows relatively weak interactions with the lipid interface, staying in the water phase in the form of homomeric coiled-coil dimers E/E.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No disattachment was observed in the additional 2.2 μs following peptide insertion. This positioning, somehow expected due to the amphipathic character of the peptide, has been reported in previous atomistic simulations of very similar fusion peptides (influenza hemagglutinin) [19] and determined by InfraRed Reflection Absorption Spectroscopy (IRRAS) measurements for LP 12 K and LP 12 E in mono-layers with an identical lipid/cholesterol composition [20].…”
Section: Lipopeptide Binding and Subsequent Effects On Membrane Propesupporting
confidence: 79%
“…This criterion is based on the concept that homomers do not play a role in fusion, meaning that their formation should be avoided. Nevertheless, there is ample experimental evidence that such aggregates do form [15,20]. The considered solitary lipopeptides thus represent a limiting case, quantified by the number of anchors n a = 1, and it is relevant to consider the situation n a N 1, i.e.…”
Section: Increasing the Lipopeptide Concentrations: The Role Of Homomersmentioning
confidence: 99%